Effectiveness of Xiakucao Oral Liquid combined with methimazole on early thyroid function recovery and treatment compliance in Graves’ disease: a real-world retrospective cohort study - Lin, Dong; Zhang, Lina; Zhang, Lu; Zhu, Jialu; Li, Houcheng; Yuan, Bichai (Frontiers in Endocrinology, 2025)
AimTo evaluate the effectiveness and treatment compliance of Xiakucao Oral Liquid (XKC) combined with methimazole (MMI) on the early recovery of thyroid function in Graves’ disease (GD) patients.MethodsIn this retrospective cohort study, GD patients receiving initial treatment at Jieyang People’s Hospital from January 2019 to December 2023 were included and divided into XKC+MMI group and MMI group based on the treatment regimen. The association between XKC+MMI and early thyroid function recovery was analyzed using multiple linear regression in the subgroup of patients with post-treatment data available at 3 months.ResultsA total of 441 patients were enrolled, among whom 113 (25.6%) patients received XKC+MMI. The proportion of patients receiving XKC+MMI was significantly higher with an initial MMI dose ≥20 mg/day than <20 mg/day (37.1% vs. 15.2%, P=0.006). In XKC+MMI group, 15 (13.3%) patients underwent continuous treatment with XKC for three months. Subgroup analysis (n=121) showed the increase of sensitive thyroid-stimulating hormone (sTSH) in XKC+MMI group was higher than that in MMI group (4.86 ± 11.7 vs 1.15 ± 5.16). Multivariate linear regression analysis indicated that compared with MMI alone, XKC+MMI was independently associated with the increase of sTSH (β=3.346, 95%CI: 0.353-6.339, P=0.031), and the continuous 3-month treatment of XKC+MMI was also independently associated with the increase of sTSH at 3 months (β=4.062, 95%CI: 0.516-7.608, P=0.027).ConclusionsXKC combination MMI treatment might promote early recovery of thyroid function. However, adherence to and persistence with XKC treatment still need to be improved.